The fetters of the sib: Weber meets Darwin - Ingela Alger; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
We analyze the effects of family ties on the incentives for productive effort. A family is modelled as a pair of altruistic siblings. Each sibling exerts effort to produce output under uncertainty and siblings may transfer output to each other. We show that altruism has a non-monotonic effect on effort. We study how this effect depends on climate, the magnitude and volatility of returns to effort. We also analyze the evolutionary robustness of family ties and how this robustness depends on climate. We find that family ties will be stronger in milder climates than in harsher climates.
Keywords: D02; D13; 330; altruism; family ties; moral hazard; evolutionary robustness; Familienökonomik; Soziales Verhalten; Altruismus; Moral Hazard; Leistungsanreiz; Leistungsmotivation; Theorie